Pharmacological Management of Allergic Rhinitis in the Elderly - Bozek, Andrzej (Drugs Aging, 2016)
Recent studies suggest that allergic rhinitis is highly prevalent in the elderly population, but is underdiagnosed and undertreated. This review article briefly introduces allergic rhinitis in the elderly (epidemiology and pathophysiology) and identifies the main goals of treatment in these patients with respect to age-related physiological factors, comorbid conditions and polypharmacy. The primary focus of the article is a narrative review of the literature concerning the different types of treatment options in elderly patients aged 60+ years (pharmacological therapy and allergen-specific immunotherapy). The main management trend for allergic rhinitis in elderly patients is the same as the trend in young patients. Second-generation antihistamines and nasal glucocorticosteroids are also the first-line therapies in seniors. In a few trials, allergen-specific immunotherapy for grass pollen or house dust mites has been shown to be effective and safe in patients aged 60 years or older with allergic rhinitis. In conclusion, undertreatment of allergic rhinitis in the elderly is a reality. Pharmacological treatment is quite similar in both older and younger patients with allergic rhinitis.